The Dynamics of the Creative Economy and Social Transformation Among Urban Gen Z in Indonesia - Fariah, Aen (Riviera Publishing, 2025)
This study explores the role of Generation Z (Gen Z) in the creative economy and its influence on social transformation in urban Indonesia. As digital natives, Gen Z is actively shaping their careers and social identities through creative industries such as digital content creation, fashion, and design. The research investigates the dual motivations driving Gen Z's involvement in the creative economy: personal fulfillment through self-expression and the pursuit of financial independence. By utilizing qualitative methods, including semi-structured interviews and focus group discussions with 30 Gen Z creators from Jakarta, Bandung, and Surabaya, the study examines how these individuals navigate the challenges and opportunities of the creative economy. Findings reveal that Gen Z's engagement with digital platforms enables them to build entrepreneurial careers, create new forms of community, and influence societal norms, particularly in areas such as gender, environmental sustainability, and social justice. However, challenges such as income instability, pressure to constantly produce content, and mental health concerns are prevalent. The study highlights the significant impact of Gen Z on reshaping urban social identities by blending global trends with local cultural elements. The research also underscores the need for targeted support in education, policy, and mental health to sustain and nurture the potential of Gen Z in the creative economy. This study contributes to a deeper understanding of how Gen Z's creative work is both economically empowering and socially transformative.